(untitled) (International Journal of Environmental Sciences, 2025)
This study aims to uncover the role of local content English education in strengthening human resources (HR) in Gowa Regency. The methodology employed is a qualitative approach through semi-structured interviews and document analysis. The findings indicate that this program successfully enhances the competencies of both teachers and students, as well as fosters students’ confidence in communication. The average national examination scores for English in Gowa Regency indicate room for improvement. This study provides recommendations for enhancing teacher training and the use of technology in education. The findings suggest that local content education can be an effective strategy for human resource development in the region.